Description of term pregnant women in labor with COVID-19: a literature review - Iman Gurnadi, Jeffry; Nur Rokhmawansyah, Zulfi; Quintina Indriyana, Sri (ACTA Medical Health Sciences, 2023)
The coronavirus disease 2019 (COVID-19) pandemic has brought a major impact to health systems and societies worldwide. However, knowledge about the effect of COVID-19 infection during pregnancy and the perinatal outcome is still limited and no specific recommendations available yet on the management of this condition. This was a literature review study on the characteristics of pregnant women, types of delivery, and neonatal outcomes associated with COVID-19. The database used as the literature source were PubMed, AJOG, NCBI, RCOG, and Google Scholar and the search was performed on the articles published from July 2021 to August 2021 that meet the inclusion criteria. Eleven articles were included in this study and were extracted and analyzed using statistic summary. The majority of the term pregnant women in labor with COVID-19 were 21-35 years old (86.4%) and 55.5% were multiparous, with the majority of them delivered their baby through caesarean section (74.3%). The perinatal outcomes demonstrated that a small percentage of newborns experienced low birth weight (10.9%) and asphyxia (3.3%). Further studies are needed regarding vertical transmission from women in labor with COVID-19 to their baby. DOI : 10.35990/amhs.v1n3.p144-149 REFERENCES World Health Organization. Coronavirus novel – China. 2020. Tersedia di: https://www.who.int/csr/don/12-january-2020-novel-coronavirus-china/en. Diakses pada 21 Oktober 2020. Perhimpunan Dokter Paru Indonesia. Pneumonia COVID-19 Diagnosis dan Penatalaksanaan di Indonesia. Jakarta: PDPI; 2020. Centers for Disease Control and Prevention. Coronavirus Disease 2019 (COVID-19). 2021. Tersedia di: https://www.cdc.gov/coronavirus/2019-ncov/covid-data/investigations-discovery/assessing-risk-factors.html. Diakses pada 22 Desember 2020. Cascella M, Rajnik M, Cuomo A, et al. Features, Evaluation and Treatment of Coronavirus (COVID-19). In: StatPearls [Internet]. Treasure Island (FL): StatPearls Publishing; 2020. Tersedia dari: https://www.ncbi.nlm.nih.gov/books/NBK554776 Laelatul U. Parity, age and gestational age links with care trimester III’s length during COVID-19. JIKK. 2020;16:133–6. Juan WJ, Ni ZY, Hu Y. Clinical chart of Coronavirus Disease 2019 in China. N Engl J Med. 2020. doi:10.1056/NEJMoa2002032. Center for Strategic and International Studies. Characteristics and Spread of COVID-19 in Indonesia: Preliminary Findings. Jakarta: CSIS; 2020. Huang C, Wang Y, Li X, et al. Clinical features of patients infected with 2019 novel coronavirus in Wuhan, China. Lancet. 2020;395(10223):497–506. doi:10.1016/S0140-6736(20)30183-5. Perkumpulan Obstetri dan Ginekologi Indonesia (POGI). Rekomendasi Penanganan Infeksi Coronavirus (COVID-19) pada Ibu Hamil. Surabaya: POGI; 2020. Yan J, Guo J, Fan C, et al. Coronavirus Disease 2019 in Pregnant Women: A Report Based on 116 Cases. Am J Obstet Gynecol. 2020;223:111.e1–111.e11. Karimi-Zarchi M, Neamimzadeh H, Dashbeb SA, et al. Vertical transmission of COVID-19 from infected pregnant mothers to neonates: A review. Fetal Pediatr Pathol. 2020;39(3):246–250. doi:10.1080/15513815.2020.1747120. Peng YD, Meng K, Guan HQ, et al. Clinical characteristics and outcomes of cardiovascular disease patients infected with 2019-nCoV. Zhonghua Xin Xue Guan Bing Za Zhi. 2020;48. Andersen AM. Fever in pregnancy and the risk of congenital malformations: A cohort study. BMC Pregnancy Childbirth. 2017;17(1):1–9. Khan S, Peng L, Siddique R, et al. Impact of COVID-19 infection on pregnancy outcomes and the risk of maternal-to-neonate transmission during birth. Infect Control Hosp Epidemiol. 2020;41(6):748–750. doi:10.1017/ice.2020.84. Yu N, Li W, Kang Q, et al. Clinical features and obstetric and neonatal outcomes of pregnant patients with COVID-19 in Wuhan, China: a retrospective, single-center, descriptive study. Lancet Infect Dis. 2020;20(5):559–564. doi:10.1016/S1473-3099(20)30176-6. Chen S, Liao E, Cao D, et al. Clinical analysis of pregnant women with 2019 novel coronavirus pneumonia. J Med Virol. 2020;92(9):1556–1561. doi:10.1002/jmv.25789. Chen H, Guo J, Wang C, et al. Clinical characteristics and intrauterine vertical transmission potential of COVID-19 infection in nine pregnant women: a retrospective review. Lancet Infect Dis. 2020;395:809–815. doi:10.1016/S0140-6736(20)30360-3. Zheng T, Guo J, He W, et al. COVID-19 in pregnancy: Two case reports on maternal and neonatal outcomes in Yichang city, Hubei, China. Medicine (Baltimore). 2020;99(29):e21334. Khan S, June L, Nawsherwan, et al. Association of COVID-19 with pregnancy outcomes in healthcare workers and general population women. Clin Microbiol Infect. 2020;26(6):788–790. doi:10.1016/j.cmi.2020.03.034. Gao L, Ren J, Xu I, et al. Placental pathology of third trimester pregnant women with COVID-19. Diagn Pathol. 2021;16(8). doi:10.1186/s13000-021-01067-6. Ferrazzi E, Poterio L, Savasi V, et al. Vaginal delivery in 5 SARS-CoV-2-infected pregnant women in Northern Italy: A retrospective analysis. BJOG. 2020;127(9):1116–1121. doi:10.1111/1471-0528.16278. Maraschini A, Corsi E, Salvatore MA, Donati S. Coronavirus and pregnancy in Italy: Results of a national population-based cohort study. Ann Ist Super Sanita. 2020;56(3):378–389. doi:10.4415/ANN_20_03_17. Arnest N, Ira S. The characteristics of pregnant women with COVID-19 at Surakarta Hospital. 2021;8:31–6. Selvi İ, Cevher FA. A retrospective analysis of clinical features, maternal and neonatal outcomes of COVID-19 cases in obstetrics clinic in Ankara, Turkey. J Obstet Gynaecol. 2021;31(2):72–76.